Stomal therapist nurses role in necrotizing fasciitis and Fournier's syndrome (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To understand the role of the stomal therapist nurses in necrotizing fasciitis through the analysis of scientific articles. Method: This is a integrative review that addressed the question: What are the scientific evidences regarding the role of the nurse enterostomal therapist in Fournier's syndrome and necrotizing fasciitis? The descriptors were selected from the Medical Subject Headings Section (MeSH), Health Sciences Descriptors (DeCS), and CINAHL Subject Headings. A bibliographic search of scientific articles was conducted in EMBASE, Medline via PubMed, Scopus, Science Direct/Elsevier, and CINAHL-EBSCO, consulted up to May 2023. Results: Thirty-three studies were included, and the main interventions identified in the studies were categorized into six categories, namely: 1) Wound care; 2) Treatment; 3) Warning signs; 4) Patient care; 5) Adjunct therapies; and 6) Nursing team's work process. Conclusion: It was possible to identify the main interventions of the stomal therapist nurses and their importance in assisting people with necrotizing fasciitis, as their interventions range from direct wound care to comprehensive patient care, as well as establishing an interprofessional work process.